Beyond inclusion and exclusion : Jewish experiences of the First World War in Central Europe - Crouthamel, Jason; Geheran, Michael, 1971-; Grady, Tim (Timothy L.); Kohne, Julia (New York ; Oxford : Berghahn, 2019)
'During the First World War, the Jewish population of Central Europe was politically, socially, and experientially diverse, to an extent that resists containment within a simple historical narrative. While antisemitism and Jewish disillusionment have dominated many previous studies of the topic, this collection aims to recapture the multifariousness of Central European Jewish life in the experiences of soldiers and civilians alike during the First World War. Here, scholars from multiple disciplines explore rare sources and employ innovative methods to illuminate four interconnected themes: minorities and the meaning of military service, Jewish-Gentile relations, cultural legacies of the war, and memory politics' --
Introduction / Jason Crouthamel, Michael Geheran, Tim Grady and Julia B. Kohne -- Hopes and Disappointments: German and French Jews during the wars of 1870/71 and 1914-1918 / Christine G. Kruger -- Habsburg Jews and the Imperial Army before and during the First World War / Tamara Scheer -- The'Stepchildren' of the Kaiserreich: Alsatians in the German Army during the First World War / Devlin M. Scofield -- Rethinking Jewish Front Experiences / Michael Geheran --'Being German' and'Being Jewish' during World War I: An Ambivalent Transnational Relationship? / Sarah Panter -- In the Shadow of Antisemitism: Jewish Women and the German Home Front during World War I / Andrea A. Sinn -- The Social Engagement of Jewish Women in Berlin during the First World War / Sabine Hank --'My comrades are for the most part on my side': Comradeship between Non-Jewish and German Jewish Front Soldiers in the First World War / Jason Crouthamel -- Blind Spots and Jewish Heroines: Refashioning the Galician War Experience in 1920s Hollywood and Berlin / Philipp Stiasny -- Agnon on the Home Front in In Mr Lublin's Store: Hebrew Fiction of the First World War / Glenda Abramson -- Paper Psyches: On the Psychography of the Front Soldier according to Paul Plaut / Julia Barbara Kohne -- Narrative negotiations: Interpreting the Cultural Position of Jews in National(social)ist War Narratives from 1914 to 1945 / Florian Bruckner -- German Jewry and World War I: Beyond Polemic and Apologetic / Derek Jonathan Penslar.
Includes bibliographical references and index.
Keywords: World War, 1914-1918 -- Jews -- Europe, Central; World War, 1914-1918 -- Participation, Jewish; Jews -- Europe, Central -- History -- 20th century; World War, 1914-1918 -- Social aspects -- Europe, Central; Europe, Central -- Ethnic relations -- History -- 20th century